Gated communities along the bank of the Danube in Budapest - Kanczlerné Veréb , Mária (4D Journal of Landscape Architecture and Garden Art, 2009)
The article based on a research work about gated communities of Budapest gives a short description of several types of new housing through some characteristic projects. Although it’s a global phenomenon, there are some ethimological problems around the name „lakópark” (close translation: „dwelling park") which is used for gated community in Hungarian, and there’s no exact definition of it.